Nanomaterials as Theranostic Agents for Cancer Therapy - Bauri S.; Tripathi S.; Choudhury A.M.; Mandal S.S.; Raj H.; Maiti P. (My University, 2025)
The concept of theranostics is ground breaking in the area of cancer remedy due to its capability to integrate both therapeutic and diagnostic elements in a single approach. This approach is advantageous due to its capability to diagnose and assess the treatment simultaneously enabling the identification of the optimum treatment course. The process includes real-time monitoring of therapeutic strategies through the simultaneous delivery of imaging and therapeutic agents. Nanocarriers or nanomaterials play a vital role in theranostic applications of the cancer therapy. The dual task provides various challenges. Imaging modalities are engineered to enhance signal-to noise ratios while being rapidly eliminated. The high-concentration accumulation of curatives at the site of the disease and biocompatibility of nanocarriers are two of the important concerns considered for design of theranostic nanostructures. Various nanomaterials have been integrated with other materials to form a composite to enhance the therapeutic efficacy along with the diagnosing ability. In this report, the overview of metal, ceramic, polymer, and small-molecule-based nanoparticulate systems are presented for theranostic applications. © 2023 American Chemical Society.